Effect of different soybean meal type on ileal digestibility of amino acid in weaning pigs - Kim, Dong Hyuk; Heo, Pil Seung; Jang, Jae Cheol; Jin, Song Shan; Hong, Jin Su; Kim, Yoo Yong (Journal of animal science and technology, 2015)
An experiment was conducted to evaluate apparent (AID) and standardized (SID) ileal digestibilities of crude protein (CP) and amino acids (AA) with 6 soybean products in weaning pigs. A total of 14 weaning barrows with an initial body weight of 6.54 ± 0.34 kg were fitted with T-cannula at the distal ileum and allotted to 7 diets containing various soybean products. The soybean products used in the experiment were conventional soybean meal (CSBM), SBM fermented by Aspergillus oryzae GB-107 (FSBMA), SBM fermented by Bacillus subtilis PP6 (FSBMB), UV sterilized SBM fermented by Bacillus subtilis PP6 (UVFSBMB), SBM containing Bacillus subtilis PP6 (PSBM), and soy protein concentrate (SPC). Six corn-based diets were used and each of soybean products was added. All diets contained 5.0 g/kg of chromic oxide as an indigestible indicator and an N-free diet was used to measure basal endogenous losses of CP and AAs. Ileal CP digestibility did not differ by different soybean products. However, SIDs of Ile, Phe and Val were improved in pigs fed the FSBMB, UVFSBMB and SPC diets and the pigs fed the FSBMA diet showed higher SIDs of Phe and Val compared with those fed the CSBM diet (P < 0.05). The FSBMB diet had higher SIDs in most AAs compared with the FSBMA diet (P < 0.05), and higher SIDs of Lys, Ala, Pro, Ser, and Tyr compared with PSBM diet (P < 0.05). However, there was no response of UV-sterilization on the FSBMB in the SIDs of AAs. These results suggest that SIDs of AAs could be improved by the supplementation of fermented soybean products in the diet for weaning pigs but fermentation with Bacillus subtilis is more efficient in improving ileal AA digestibility than that with Aspergillus oryzae . Furthermore, probiotics supplementation in the CSBM and UV-sterilization of the FSBMB had no effects on chemical composition and ileal AA digestibility.